A study on awareness level of workers in using Personal Protective Equipment (PPE) at construction site / Daniel Iskandar Hakimie Mohammad Roshidi - Mohamad Roshidi, Daniel Iskandar Hakimie (2021)
Construction industry is always known as an economic engine in every nation where it really plays a major and vital role in generating income and directly increase the job opportunities to the citizens. Despite being the contributors to the economic growth in Malaysia, construction industry also known as the most dangerous and hazardous workplace towards the workers where it will harm and cause injuries to them which also can lead to death if the dangers and risks are not managed well. There are many accidents that occur at the construction site due to the negligence of the workers in not implementing the Personal Protective Equipment (PPE) at the construction site. PPE is the equipment to protect the construction worker from any injuries, accidents, and fatalities. Implementation of PPE is very important for any person either the worker or visitor once they enter the construction site. PPE also should be choose wisely depending on the requirement of the work, and depending on the work environment which require PPE to function as desired, clean and ready when needed. Therefore, the aim of this research is to identify the current safety practice in using PPE at construction site in Malaysia. The objectives of this research are to evaluate the awareness level of workers regarding the PPE practice at construction site, and to identify the challenges to practice the PPE practice at construction site. The method use for collecting data is by carry out online questionnaire survey form and distributed to the person who involve in construction industry. The questionnaire had been respond by 64 number of respondents. The data obtained from the survey is evaluated to achieve the objectives of the research.